MODEL RAPID APLICATION DEVELOPMENT PADA SISTEM INFORMASI AKUNTANSI PENGGAJIAN PT ADC - Jovina Puspita Dewi Wulandari; Feri Prasetyo (Universitas Islam Nahdlatul Ulama Jepara, 2023)
Arunika Digital Consulting (ADC) is a company in the startup phase of IT consulting covering various industries such as digital technology, digital printing, and consulting. The company manages employee salaries as a percentage of profits, which is then recorded by entering employee salary data into Ms. Excel. This system can cause many errors such as lack of time to manage employee payroll information and an ineffective employee payroll system to prepare the company to a greater level, so a facility is needed that can solve this, because with the computerized system it is expected to obtain information accurately, quickly and efficiently with time, Faster, more precise and accurate labor and costs and employee salary calculations. This research data was obtained using field research methods through observation, interviews and literature studies and for the development of this design software, researchers used the RAD (Rapid Application Development) method. The results of this study will provide information that with the implementation of the Payroll Information System, it can provide several positive things, namely, preparing a more efficient, fast, and accurate employee salary calculation for a wider level of the company. And test the process using User Aceptance Testing